PELAYANAN ADMINISTRASI PERPAJAKAN DI KANTOR PELAYANAN PAJAK PROVINSI MALUKU UTARA - Dutu, Remeyl; Tampi, Gustaf Budi; Pombengi, Jericho Danga (Sam Ratulangi University, 2018)
Abstrak: Tax Administration Service at North Maluku Province Tax Office. The method used in this researchis qualitative research method where the data is presented in descriptive form to then analyzed, data collectionis done by direct interview to the research informant which have been determined by purposive sampling method,observation in the field and by reviewing supporting documents. Public services as all forms of activitiesundertaken by central government agencies, in regions in the form of goods and services both in the fulfillmentof community needs and in the implementation of legislation.administration is a dynamic and sustainable process, driven in order to achieve goals by utilizing peopleand materials through coordination and cooperation. Taxes are the contribution of the people to the statetreasury under the law (which can be imposed) by not receiving lead services (kontraprestasi) which can bedirectly demonstrated and used to pay public expenditures. Given the importance of the tax role, the governmentin this case the Directorate General of Tax under the auspices of the Ministry of Finance made various strategicefforts to maximize tax revenues and tax services to the public as taxpayers. One way to do this is byimplementing modern tax administration system. Modern tax administration system is the desire to form a clean,professional, responsible, and able to create an effective and efficient bureaucracy. Universally, taxadministration is the key to success in a tax policy. Therefore, tax administration reform should be donecontinuously so that the service function can be given optimally to the community. With a good administrativesystem, it is expected that the government is able to optimize the realization of tax revenue and improve taxcompliance.Keywords: Public Service, Tax Administration